PENGARUH INFORMASI ARUS KAS DAN LABA BERSIH TERHADAP VOLUME PERDAGANGAN SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR OTOMOTIF YANG TERDAFTAR DI BEI PERIODE 2009-2012 - Maulidasari, Dini Nurul (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2020)
This study aims to determine the effect of cash flow information and net income on stock trading volume in Automotive Sector Manufacturing Companies listed on the Indonesia Stock Exchange (BEI) 2009-2012 period. The variables used in this research are cash flow (variable X1), net profit (variable X2), and stock trading volume (variable Y). The research method used in this research is associative with a quantitative approach. The population in this study is the Manufacturing Financial Report on the IDX. By using secondary data collection techniques, the sample used is the Cash Flow Statement and the Profit and Loss Statement of Manufacturing Companies listed on the IDX from 2009 to 2012. From the test results, it can be seen that the independent variable can simultaneously explain the dependent variable by 70.3% while the remaining 29.7% is influenced by other variables outside the model tested in this study. And the results of hypothesis testing partially show that cash flow has a positive and significant effect on Stock Trading Volume. And Net Profit has a positive and significant effect on Stock Trading Volume. The results of the hypothesis simultaneously show that cash flow and net income have a significant effect on stock trading volume.